MEANINGS OF LIFE AND DEATH AMONG CARDIAC PATIENTS AND THEIR CAREGIVERS: AN INTEGRATIVE REVIEW - Camilo dos Santos, Solange; Alves de Oliveira, Esmael (Cadernos ESP, 2025)
This article is part of a master's research developed in the Graduate Program in Psychology at a federal public university located in the interior of the state of Mato Grosso do Sul, with the aim of understanding the meanings of life and death among both individuals affected by heart diseases and their caregivers. As a preliminary investigation procedure, an integrative review was conducted to understand the state of the art on the topic using the databases Virtual Health Library, Google Scholar, CAPES Journal Portal, and PubMed, focusing on Portuguese-language and open access works. Out of a total of 4,178 publications found, 23 articles were selected after reading the titles and abstracts. From these, a final sample of 18 manuscripts was obtained. The research findings highlighted the fundamental role of emotions in coronary disease. In conclusion, the importance of the integrative review is emphasized both for understanding Brazilian academic production on chronic diseases and as an important tool for detecting possible gaps to be addressed in future research. It is believed that such reflections can contribute not only to the field of health psychology but also to the field of studies and research on chronicity and care practices.
Keywords: Psychology; Heart disease; Meanings; Life; Death